The Correlation between Students’ Self-Regulated Learning Strategies and their Writing Ability in Argumentative Writing Class - Nur Zikri Amalia; Lies Amin Lestari; Syafi'ul Anam (International Journal of Pedagogy and Teacher Education, 2023)
This study investigates the use of self-regulated learning strategies by students at a public university in Surabaya and examines the relationship between these strategies and their performance in argumentative writing classes. The sample comprised 57 students of both genders, selected through convenience sampling, and representing various academic years. All participants had previously completed an argumentation class. To achieve the study’s objectives, the Self-Regulated Learning Questionnaire (WSSRLQ) was adapted to meet the specific needs of the study, and students' argumentative writing scores were analyzed correlationally. The reliability of the questionnaire was confirmed with a Cronbach's alpha of 0.830. Results indicate that metacognitive strategies were the most frequently employed, particularly in guiding planning and improving the quality of writing assignments. Students also utilized cognitive strategies focused on language elements, social-behavioral strategies, and motivational strategies to enhance their writing performance. The study revealed a strong correlation between cognitive strategies and writing performance, a moderate correlation for metacognitive and motivational strategies, and no correlation for social-behavioral strategies. Overall, a weak correlation was observed between self-regulated learning strategies and overall writing abilities.